THE IMPACT OF GLOBAL MARKET VOLATILITY ON THE FINANCIAL RESILIENCE OF AGRIBUSINESS ENTITIES: RISK ASSESSMENT AND ADAPTIVE MITIGATION FRAMEWORKS - Kavun, Valentyna (Global Prosperity, 2026)
Abstract. This article examines the transition from static stability to the concept of dynamic financial resilience as a core survival factor for contemporary agribusiness entities. The research objective is the identification of structural determinants of financial vulnerability and the development of an adaptive risk mitigation mechanism amidst the financialization of commodity markets. The methodological framework of the study encompasses econometric modeling (VAR, GARCH), impulse response analysis and Monte Carlo simulations. For the first time, the article presents the proprietary integrated model “Agrosystem Kavun”, which ensures the multimodal convergence of financial instruments, AgTech solutions and ESG determinants. The findings substantiate that active resilience, predicated on predictive analytics and strategic optionality, facilitates the neutralization of the price-cost squeeze effect and preserves the institutional sovereignty of the enterprise. The study justifies the transformation of risk management into a proactive strategy, where technological determinism and managerial cognitive flexibility foster the business`s intellectual immunity, ensuring long-term leadership under conditions of global uncertainty.